Vibrio Cholerae as it Relates to Food and Health - Cortes-Sanchez, Alejandro De Jesus; Diaz-Ramirez, Mayra; Villanueva-Carvajal, Adriana; Martin-Azocar, Alejandra L. San (Pakistan Journal of Nutrition, 2016)
Nutrition is a fundamental human need; therefore, food, because it provides vital nutrients, must be safe guarded. Food borne diseases are an important worldwide public health issue because of their high incidence and mortality. Cholera is a Food borne disease caused by the bacterium Vibrio cholerae that is contracted by ingesting raw or poorly processed foodstuff, in particular seafood. Currently, to aid in reducing cholera incidences and isolating and detecting V. cholerae in foodstuff, protocols and analytical methodologies have been developed for use by food processors and regulatory offices to maintain food monitoring and safety controls. The principal objective of these measures is to maintain food safety for the consumers. In the present study, Food borne diseases are described in a general manner, with a focus on cholera and the characteristics of its causal agent, Vibrio cholerae. Analytical methods for the phenotypic and molecular detection of V. cholerae in contaminated foods are also discussed.